Residual stress, thermomechanics & infrared imaging, hybrid techniques and inverse problems, Volume 8 : Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics - Sasso, Marco; Connesson, Nathanael; Singh, Raman; DeWald, Adrian; Backman, David; Gloeckner, Paul; Rossi, Marco (Conference Proceedings of the Society for Experimental Mechanics Series, 2014)
This critical collection presents early findings and case studies on a wide range of areas, as presented in  the Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics. The collection includes papers in the following general technical research areas: • Advances in Residual Stress Measurement Methods • Residual Stress Effects on Material Performance • Optical, Ultrasonic, and Diffraction Methods for Residual Stress Measurement • Thermomechanics & Infrared Imaging • Inverse Methods • Inverse Methods in Plasticity • Applications in Experimental Mechanics Residual Stress, Thermomechanics & Infrared Imaging, Hybrid Techniques and Inverse Problems: Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics is the eighth volume of eight from the Conference.